Repetition in Literary Arabic: Foregrounding, Backgrounding, and Translation Strategies - Jawad, Hisham (Meta, 2009)
AbstractThe paper investigates lexical repetition in Arabic original literary texts and English translations. The empirical base material consists of a three-part autobiography (al-Ayyām, by Tāhā Hussein) and its translation (The Days). The method involves a mapping of the target text (TT) onto the source text (ST) so as to see how instances of lexical repetition are rendered into the translations and what are the strategies and norms involved in determining certain translation choices. Three types of lexical repetition are studied: lexical-item repetition, lexical-doublet repetition and phrase repetition. Lexical repetition serves two major functions, namely textual and rhetorical. The textual function concerns the potential of repetition for organising the text and rendering it cohesive, while the rhetorical foregrounds a mental image or invokes emotions in emotive language. It is observed that the translation of the autobiography’s second part is characterised mainly by the absence of lexical repetition, contrary to the translations of the first and third parts. Thus, the target text misrepresents the original author as passing through three stages of textual, stylistic development. As to the translation strategies, the findings suggest that the translators vary the ST by using different patterns of reference. Rhetorical repetition is backgrounded by at least one translator who replaces it with pervasive variation. It is argued that the ambivalence of their approaches leads to a misrepresentation of the original text (and perhaps the author) as rather uneven.The strategies for translating lexical repetition highlight the translators’ individual attitudes towards the ST’s norms and their adherence to the linguistic and cultural norms prevalent in the TL environment. On the whole, there is a variation in the degree of bias towards the norms of either SL or TL. In terms of Toury’s norms model, it may be safe to claim that the general trend of translational norms seems to lean more towards the acceptability pole than the adequacy pole, i.e., a TL-oriented strategy is opted for.